(untitled) (Semiárida, 2026)
Montia fontana L. (Montiaceae) is a cosmopolitan species associated mainly with wet habitats, whose broad morphological variability has led to different taxonomic interpretations over time. In Argentina, its known distribution included the Malvinas Islands and the provinces of Jujuy, San Juan, Neuquén, Río Negro, Chubut, Santa Cruz, and Tierra del Fuego. The aim of this study was to document the first record of M. fontana for La Pampa Province, provide a description based on local material, and update its geographic distribution in Argentina. Specimens were collected at El Carancho Lagoon (Utracán Department, La Pampa), processed using standard botanical techniques, and identified through specialized literature and comparisons with material from digital herbaria. A population of M. fontana was recorded growing in seasonally flooded areas along the lagoon shoreline. The specimens exhibited diagnostic characters consistent with the species, although some traits differed from previous descriptions reported for the Argentine flora, a finding that agrees with the high morphological variability previously documented for this taxon. This record extends the known distribution range of the species in Argentina and represents the second record of a Montiaceae species for La Pampa Province. Furthermore, the occurrence of the species in a wetland associated with plant communities tolerant of moderate salinity suggests a broader ecological amplitude than generally attributed to the species. This new record contributes to the knowledge of the flora of La Pampa and highlights the importance of continued botanical exploration of regional wetlands to improve our understanding of the distribution of uncommon plant species in central Argentina.